ANTIFUNGAL SUSCEPTIBILITY TESTING: CURRENT ROLE FROM THE CLINICAL LABORATORY PERSPECTIVE - Brunella Posteraro; Riccardo Torelli; Elena De Carolis; Patrizia Posteraro; Maurizio Sanguinetti (Mediterranean Journal of Hematology and Infectious Diseases)
Despite availability of many antifungal agents, antifungal clinical resistance occurs, perhaps as a result of an infecting organism found to be resistant in vitro to one or more antifungals tested. Thus, antifungal susceptibility testing (AFST) results, if timely generated by the clinical microbiology and communicated to clinicians, can aid them in the therapeutic decision making, especially for difficult-to-treat invasive candidiasis and aspergillosis. Although recently refined AFST methods are commercially available to allow a close antifungal resistance surveillance in many clinical setting, novel assays, relying on short-time antifungal drug exposure of fungal isolates, are upcoming tools for AFST. Based on emerging technologies such as flow cytometry, MALDI-TOF mass spectrometry, and isothermal microcalorimetry, these assays could provide a reliable means for quicker and sensitive assessment of AFST.